Mobiliário infantil: conceito de uma cama Montessori - Batista, Fernanda Gasparoti (2018)
The present research is based on Montessori pedagogical methodology. Created by Maria Montessori, this is a set of theories, practices and didactic materials. According to Montessori, the most important fact is not the material or the practice, but the possibility of developing the child's abilities from the evolution of each. From this, the proposal is the development of a children's furniture - a bed - from the study proposed by Montessori, considering characteristics of child development, children's furniture and ergonomics. The projects a product that contributes to the child developing in its ‘natural time’ with freedom and autonomy.